The Impact of Poverty and Capital Expenditure on The Human Development Index in North Sumatra - Murbanto Sinaga; Rika Surianto Zalukhu (International Journal of Economics and Management Research, 2022)
Human development in north Sumatra is showing progress. However, the human development disparity in the North Sumatra province is still showing. The problem must be overcome quickly to prevent further disparity from developing. The study was to analyze the impact of poverty and capital expenditure on Human Development Index (HDI) of regency/city in North Sumatra. This study uses quantitative descriptive methods which have been provided by previous study conducted on 33 regencies/cities in the North Sumatra. The data covers the poverty rate, capital expenditure and HDI of regency/city in North Sumatra in 2019. Data was accessed online on the Central Statistical Agency (BPS) for North Sumatra Province website. Data analysis method using multiple linear regression analysis method. Analysis shows that poverty has a negative and significant impact on HDI of regency/city in North Sumatra. Meanwhile, capital expenditure has a positive and insignificant effect on of regency/city in North Sumatra. Poverty and capital expenditure are simultaneously significant on HDI of regency/city in North Sumatra. The result of this study implicates allocation of capital expenditure and the creation of human development strategies for the district or city in the north Sumatra province.